Application of the 3D-MRI on post-operative graft assessment in adolescent patients with ACL reconstruction: A minimal 2-year follow-up - Wang, Xiaona; Qi, Yansong; Bao, Huricha; Xu, Yongsheng (Frontiers in Surgery, 2023)
Background: The purpose of the present study was to assess the prognostic morphological changes of the reconstructed hamstring auto-grafts by using reconstructed three-dimensional MRI (3D-MRI) in adolescent patients with ACLR. Methods: 22 adolescent patients (less than 17 years old) were retrospective included between January 1, 2018, and October 31, 2020, in our department. The patients were divided into 2 subgroups: subgroup A (< 14 years old) and subgroup B (≥14 years old). 3D-MRI was used to detect the total cross-sectional area (TCA) and long-to-short axis (LSA) ratio of the reconstructed ACL graft at the proximal, mid-point, and distal regions. The minimal follow-up was 2 years. Results: The averaged follow-up of subgroup A and B was 37.8±5.6 and 37.6±6.5 months, respectively. Comparing to the initial graft (ACLR operation), the TCA of reconstructed ACL was increased by 30.6 % on average, and the TCAs at proximal, mid-point, and distal regions were increased by 56.4%, 50.0%, and 17.7%, respectively, inner-group comparisons showed that the TCAs of the 3 region in subgroup A were all increased at the follow-up (P=0.002) (P<0.001) (P<0.001), however, only increased mid-point (P=0.024) and distal TCAs (P<0.001) were found in subgroup B. Comparing to the native ACL, the proximal LSA ratio in subgroup A was comparable, while it was lower in subgroup B than the native ACL (P=0.004), the distal LSA ratios in the 2 subgroups were both lower than the native ACL (P=0.004) (P=0.006). Conclusions: 3D-MRI assessment can exactly identify the morphological changes of the graft in adolescent patients with ACLR, the TCA of the constructed ACL was increased compared to the initial graft, however, the LSA ratio was still lower than the native ACL. Younger adolescent patients may have a better potential on the ligamentization after ACLR than the older adolescent patients.